Formulation and Evaluation of Tadalafil- Loaded Nano-Ointment and Cream for Raynaud’s Phenomenon - Somaskandan, Subramanian (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The research is to prepare and characterize the tadalafil (TDL) loaded cream and nano-ointment for the localized treatment of Raynaud’s phenomenon (RP). As far now, there is no marketed topical TDL formulation available for RP, a conventional ointment loaded with TDL was prepared which is used to compare with the TDL cream and nano-ointment formulation. This study compares in vitro and ex vivo data for TDL-loaded cream and nano-ointment along with the conventional ointment for the RP. Both formulations were assessed for spreadability, as well as in vitro and ex vivo release studies and drug release kinetics models. The objective was to ascertain which formulation is more effective for treating RP by penetrating deeper into the skin surface. Materials and Methods: The TDL cream was prepared with a high-speed homogenizer technique and evaluated for pH, viscosity, spreadability, and drug release studies in both in vitro and ex vivo through snake shed skin. The nanoparticles were prepared by ionic gelation technique and characterized, then loaded into the simple ointment base and then evaluated for pH, spreadability, and drug release studies in both in vitro and ex vivo through snake shed skin. Results and Discussion: The TDL-loaded nano-ointment was determined to be the superior formulation when compared to TDL-loaded cream. This conclusion stemmed from the ability of nano-ointment to sustain release for more than 120 min, surpassing the performance of the cream. The superiority also attributed to the nano-ointment spreadability, pH, nano-size, and longer contact time with the skin which may exhibit deeper penetration into the skin. Conclusion: The TDL-loaded nano-ointment may provide an effective treatment for RP while potentially reducing the systemic side effects associated with oral administration.